2016
DOI: 10.1038/eye.2016.95
|View full text |Cite
|
Sign up to set email alerts
|

Aflibercept in persistent neovascular AMD: comparison of different treatment strategies in switching therapy

Abstract: Purpose To evaluate the effects of aflibercept administered according to a pro re nata (PRN) or Fixed Regimen to patients with neovascular AMD and persistent intraretinal/ subretinal fluid (IRF/SRF) despite three consecutive ranibizumab injections. Methods Patients were switched to aflibercept injection (IVA) administered according to a PRN or to a fixed regimen for 1 year in two different retina centers. At baseline each patient underwent a complete ophthalmologic evaluation, including bestcorrected visual ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
2
8
1
Order By: Relevance
“…However, bimonthly injections provided BVCA improvement while patients in the PRN group only had stabilized visual acuity. Our good results with a fixed bimonthly protocol are consistent with a recent study by Ricci and al (10). In this study, the authors compared both treatment protocols, but in eyes treated with aflibercept after a switch from ranibizumab.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, bimonthly injections provided BVCA improvement while patients in the PRN group only had stabilized visual acuity. Our good results with a fixed bimonthly protocol are consistent with a recent study by Ricci and al (10). In this study, the authors compared both treatment protocols, but in eyes treated with aflibercept after a switch from ranibizumab.…”
Section: Discussionsupporting
confidence: 93%
“…Only one recent study reported the effects of these 2 regimens in cases of a switch from ranibizumab to aflibercept in recurrent nAMD. In this study, the bimonthly protocol used after the switch seemed more efficient than PRN usage (10).…”
Section: Introductionmentioning
confidence: 76%
“…Reported outcomes included BCVA changes and stability, changes in CRT, macular volume, and PED height. Overall, we included 8 prospective2229 and 203049 retrospective studies, with a mean follow-up of at least 6 months after converting to aflibercept. Two articles included the same eyes at different times after conversion 23,24…”
Section: Resultsmentioning
confidence: 99%
“…Some of the studies showed visual improvements,19,20,44 but others failed to include this information 21,25,43. The difference in treatment protocols may be one of the reasons for the different visual outcomes among the studies 45,46.…”
Section: Discussionmentioning
confidence: 99%